2017
DOI: 10.5455/jtomc.2017.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the frequency of growth retardation in pediatric out patients with growth retardation complaints

Abstract: Aim: Having a healthy child is the most basic concern for parents, and their children being ill or showing signs of illness therefore causes them anxiety. Parents cannot generally be objective in assessing the growth of their own children. Children's growth must be evaluated solely with appropriate measurements and assessment criteria. The purpose of this study is to investigate the growth of patients with suspected retarded growth presenting to the children's health and diseases clinic. Material and Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
0
1
Order By: Relevance
“…The present findings show that longer (19 months) duration of symptoms was significantly correlated with the presence of GR in the patients with CD compared to patients without GR (12 months). Whereas one study reported that 78% of 100 patients with GR as the presenting sign were not diagnosed with GR, 22 in the present study 76.3% of patients that presented with GR were medically diagnosed with GR ( P < 0.001). Moreover, as expected, the short duration (<2 years) of breastfeeding was also significantly correlated with the presence of GR.…”
Section: Discussioncontrasting
confidence: 79%
“…The present findings show that longer (19 months) duration of symptoms was significantly correlated with the presence of GR in the patients with CD compared to patients without GR (12 months). Whereas one study reported that 78% of 100 patients with GR as the presenting sign were not diagnosed with GR, 22 in the present study 76.3% of patients that presented with GR were medically diagnosed with GR ( P < 0.001). Moreover, as expected, the short duration (<2 years) of breastfeeding was also significantly correlated with the presence of GR.…”
Section: Discussioncontrasting
confidence: 79%